ESTIMASI POLA DISPERSI DEBU, SO2 DAN NOX DARI INDUSTRI SEMEN MENGGUNAKAN MODEL GAUSS YANG DIINTEGRASI DENGAN SCREEN3 - Ni Wayan Srimani Puspa Dewi; Tania June; Mohammad Yani; Mujito Mujito (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Industrial activities are sources of air pollution. Pollutants dispersion in air influenced by meteorological condition, such as wind speed, wind direction, air temperarture, air turbulence and atmospheric stability. Air quality monitoring is important in controling the worst condition of pollutants concentration. Air quality monitoring is not easy to do, because it is time consuming, costly and need technology, so that air quality model is developed as an alternative air quality monitoring. This research used gaussian model, a model for predicting pollutant concentrations in downwind area. This model is applied in cement industry, focusing on major pollutants of the cement industry. Sources of pollutants consist of dust, SO2 and NOx. The modeling results showed maximum ground level concentration of dust, SO2 and NOx occur at night (7-10 PM). The maximum ground level concentration of dust, SO2 and NOx at night respectively were 13.16 μg / Nm3, 32.69 μg / Nm3, 100.21 μg / Nm3 (N1 stack) and 14.65 μg / Nm3, 36.65 μg / Nm3, 128.10 μg / Nm3 (N2 stack) based from downwind scenarios at night when atmospheric condition was stable. The distance where the maximum ground level concentration occured has a strong correlation with wind speed (-0.82 ≤ r ≤ -1). Based on gaussian model output, air quality monitoring should be executed at night time (stable atmospheric condition) and located at ground level where maximum concentration occured. Increasing 50m of stack can decrease 57% pollutant concentrations in stable condition.